English words: Islamic definitions - Abdul Rashid, Alwa; Othman, Khairiah (2014)
Some words have different semantic values from one community to the other. The fact that the English language is one of the main languages widely used by Muslims, it needs to be able to adequately express the Islamic worldview. The study aimed to examine some words in an English dictionary which meanings contradict the Islamic worldview. The English dictionary, namely the Cambridge Advanced Learner’s Dictionary (2008), was examined qualitatively using a document analysis. Analyses were based on the Quranic verses, hadiths or traditions of the Prophet (may peace be upon him) with special focus on the hadiths of al-Bukhari and Muslim which are deemed as among those ranked the highest. Viewpoints from the consensus of the ulamas or learned scholars were also sought. The findings revealed that thirty-three words were defined contradictory to the Islamic principles. The study has pedagogical implications on teaching English to Muslim learners.